2016
DOI: 10.1007/s11764-016-0588-6
|View full text |Cite
|
Sign up to set email alerts
|

Screening for thyroid cancer in survivors of childhood and young adult cancer treated with neck radiation

Abstract: Background The optimal method of screening for thyroid cancer in survivors of childhood and young adult cancer exposed to neck radiation remains controversial. Outcome data for a physical exam-based screening approach are lacking. Methods We conducted a retrospective review of adult survivors of childhood and young adult cancer with a history of neck radiation followed in the Adult Long-Term Follow-Up Clinic at Memorial Sloan Kettering between November 2005 and August 2014. Eligible patients underwent physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 48 publications
1
16
0
1
Order By: Relevance
“…Currently, guidelines for cancer survivors do not advocate this practice and recommend yearly physical examination only [121, 123]. A recent study by Tonorezos et al[94] found that annual physical exam was sufficient to screen for thyroid cancer, and the authors concluded that the harms of screening (expense, invasive procedures, and anxiety) could be safely reduced if practitioners caring for cancer survivors at risk for thyroid cancer focus on the physical exam of the neck instead of costly imaging. In asymptomatic adult patients (notably not cancer survivors), ultrasonography of the neck and subsequent fine needle aspiration biopsy can certainly diagnose thyroid cancer, but it is unclear if screening can decrease mortality rates or improve patient health outcomes, whereas treatment of indolent thyroid malignancies that are identified by screening may increase the risk of patient harm [127].…”
Section: Screening and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, guidelines for cancer survivors do not advocate this practice and recommend yearly physical examination only [121, 123]. A recent study by Tonorezos et al[94] found that annual physical exam was sufficient to screen for thyroid cancer, and the authors concluded that the harms of screening (expense, invasive procedures, and anxiety) could be safely reduced if practitioners caring for cancer survivors at risk for thyroid cancer focus on the physical exam of the neck instead of costly imaging. In asymptomatic adult patients (notably not cancer survivors), ultrasonography of the neck and subsequent fine needle aspiration biopsy can certainly diagnose thyroid cancer, but it is unclear if screening can decrease mortality rates or improve patient health outcomes, whereas treatment of indolent thyroid malignancies that are identified by screening may increase the risk of patient harm [127].…”
Section: Screening and Managementmentioning
confidence: 99%
“…Based on the underlying evidence as well as the potential benefit gained by early detection and appropriate management, the panel concluded that neither thyroid ultrasound nor neck palpation was superior. Given the data that radiation-induced PTC is primarily confined to the neck and has an excellent long-term prognosis similar to sporadic PTC [90-94], it is the author’s current practice to use physical examination as the primary screening modality. Routine palpation should identify a clinically significant cancer while minimizing the unnecessary anxiety, testing, and health care costs that result from the ultrasonographic identification of a subclinical thyroid nodule.…”
Section: Screening and Managementmentioning
confidence: 99%
“…Among 585 patients with neck radiation, seven survivors developed papillary thyroid carcinoma (PTC). This indicates that, in adult survivors of cancer during their childhood or young adulthood with a history of radiation therapy to the neck for cancer, an annual physical exam should be considered appropriate as a thyroid cancer screening strategy [ 19 ]. Patients with head and neck squamous cell carcinoma showed a strong incidence of a subsequent primary thyroid cancer during the first 5 years after diagnosis and IR-treatment, supporting the concept that continued surveillance of thyroid status is important in this scenario [ 20 ].…”
Section: Sensitivity Of the Thyroid Gland To Radiation And Cancer mentioning
confidence: 99%
“…Exposure to radiation during childhood is considered to be a predictor for thyroid malignancy, including follicular neoplasms, because the sensitivity of the thyroid gland to radiation is significantly greater [ 32 ]. A recent study from Belarus described such an association [ 33 ]. However, the risk of getting thyroid cancer may persist for many decades after radiation exposure, and an annual physical examination should be thus encouraged as a thyroid cancer screening strategy [ 34 ].…”
Section: Main Textmentioning
confidence: 99%